Genetic Diversity of Mudskipper Species (Periophthalmus spp.) from the Southern Coast of Java, Indonesia, Based on the Mitochondrial 16S Gene - Arisuryanti, Tuty; Nuraliyah, Tasya; Dwijayanti, Vindi; Aji, Katon Waskito; Priyono, Dwi Sendi; Daryono, Budi Setiadi (Bogor Agricultural University, Indonesia, 2025)
The genus Periophthalmus (Bloch and Schneider, 1801) comprises a diverse group of mudskippers within the family Oxudercidae and subfamily Oxudercinae. It includes 20 verified species globally, with 11 of these species originating from Indonesia. Among them, P. kalolo and P. argentilineatus are prevalent across seven major islands. However, P. novemradiatus is less documented, with limited distribution records. The morphological similarities among Periophthalmus spp. complicate recognition, often leading to misidentification. To address this challenge, this study investigated the phylogenetic relationships and genetic diversity among these three species, utilizing the 16S rRNA gene as a marker. PCR amplification of the DNA from samples collected from seven regions along Java's southern coast employed primers 16Sar and 16Sbr. Phylogenetic analysis revealed three monophyletic clades corresponding to each species, with genetic divergences ranging from 3.66 to 5.40%. P. argentilineatus displayed a relatively high intraspecific divergence of 0.21-2.26%, suggesting the potential identification of cryptic species within this lineage, even with a conserved gene like 16S rRNA. We identified 47 variable sites within the 552-bp 16S rRNA sequence, including four singleton sites and 43 parsimony-informative sites. We discovered a unique marker at position 172 that could serve as a genetic identifier for distinguishing these species. These findings suggest that the 16S rRNA gene has potential as an alternative marker for species identification while also revealing genetic diversity, thereby complementing or even serving as an alternative to the commonly used COI gene in Periophthalmus spp.